Being Perceived as a Vital Force or a Burden: The Social Utility-Based Acceptance/Rejection (SUBAR) Model - Dambrun, Michael (Frontiers in Sociology, 2024)
This paper proposes a new theoretical model to explain the acceptance/rejection of agents (co-workers) and various social groups (people with mental disorders or disabilities, the elderly, the unemployed/poor, ethnic minorities) in a given social system: the social utility-based acceptance/rejection (SUBAR) Model. Based on a social utility approach, it is proposed that human social cognition evaluates and reacts to agents/groups in a social system on the basis of the perceived strengths and significant contributions they bring to the system (upward forces; e.g., skills, resources, willingness) and the perceived weaknesses that may harm the system (downward forces; e.g., use of social benefits, dependence). While the perception of upward forces for the system (i.e., vital forces) is accompanied by acceptance (positive attitudes and behaviors), the perception of downward forces (i.e., burdens on the system) promotes rejection (negative attitudes and behaviors). The combination of the two indicators predicts that low vital forces/high burden targets will be the most rejected and high vital forces/low burden targets will be the most accepted. The high burden/high vital forces and low vital forces/low burden targets should be evaluated at an intermediate level between the other two. This naive calculation of the forces exerted by agents/groups in a social system is moderated by various variables (scarcity of economic resources, values) and responds to a functional attempt to regulate individual and collective interests, themselves dependent on the efficiency of given systems. Finally, the relationship of the SUBAR model to other relevant theories will also be discussed.